Factors Contributing to Effective Implementation of Competence Based Education and Training : A moderating effect of Information and Communication Technology; A Case of Selected VET and NACTE Colleges in Mbeya-Tanzania - Kaula Stephen (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
The study aimed at assessing the factors for effective implementation of competence Based Education and Training (CBET) where Information and Communication Technology (ICT) was a mediating variable. The study was carried out in Mbeya from four selected VET and NACTE Colleges including Kyela Polytechnic College; VET and NACTE College; VET-Mbeya Zonal Office; and KAP’S Community Development Institute. The causal-effect design was applied while cluster sampling was used to drive to 300 sample of Tutors, Principals, Deputy Principal- Academic, Registrars and management from a total of 1,200. Data from the obtained sample frame was collected using questionnaire. The collected data were subjected to data cleaning and normality testing. Moreover the cleaned data were subjected for factor analysis, reliability and validity testing through SEM employment. From the analysis, it was found that ICT positively and significantly moderate students’ centered teaching curriculum, learning by doing and discoveries in effective and quick adoption and implementation of CBET. It is from this innovation what this study recommends that VET and NACTE Colleges have to adopt and use ICT technologies for quick and effective implementation of CBET.